On the courtship, breeding behaviour and vocalisation of Rhinella ornata (Spix, 1824) (Anura, Bufonidae): a well-marked escalated behaviour in a lek-like system - Costa, Fabiana R.; Moura, Pedro Henrique A. G. [UNESP]; Nunes, Ivan [UNESP] (Springer Nature, 2020)
Courtship and breeding behaviour of anurans is species-specific and defined by vocalisation, although breeding activities are still understudied for many species. Here, we describe the courtship behaviour and unpublished associated vocalisation (release and aggressive calls) of Rhinella ornata at a degraded area of the Brazilian Atlantic Rainforest within Xixová-Japuí State Park (PEXJ). Fifteen subjects distributed in five subgroups in the same lek-like systems were observed during two consecutive nights in September 2015, totalling eight fieldwork hours. A total of 79 vocalisations were analysed, and the behavioural sequence of activities carried out by the subjects was described. Results show a pattern regarding the behavioural sequence exhibited by males, starting with the arrival of the resident male at the calling site and its vocalisation to an intruder male. Although this sequence did not vary between the five observed groups, a slight difference in the time they started was reported, but with a narrow range. We also provided the first description of the release call for this species. The overall behavioural tactics of R. ornata to approach females seem uncommon among bufonids. Although further investigation is required to better understand additional aspects of the courtship and breeding behaviour of R. ornata, our findings improve the overall understanding of this species’ biology.
Keywords: Acoustic communication; Bufonidae; Courtship; Reproductive behaviour; Toads